Insulin-degrading enzyme regulates insulin-directed cellular autoimmunity in murine type 1 diabetes - Bessard, Marie-Andrée; Moser, Anna; Waeckel-Énée, Emmanuelle; Lindo, Vivian; Gdoura, Abdelaziz; You, Sylvaine; Wong, F. Susan; Greer, Fiona; van Endert, Peter (Frontiers in Immunology, 2024)
Type 1 diabetes results from the destruction of pancreatic beta cells by autoreactive T cells. As an autoantigen with extremely high expression in beta cells, insulin triggers and sustains the autoimmune CD4+ and CD8+ T cell responses and islet inflammation. We have previously shown that deficiency for insulin-degrading enzyme (IDE), a ubiquitous cytosolic protease with very high affinity for insulin, induces endoplasmic reticulum (ER) stress and proliferation in islet cells and protects non-obese diabetic mice (NOD) from diabetes. Here we wondered whether IDE deficiency affects autoreactive CD8+ T cell responses to insulin and thereby immune pathogenesis in NOD mice. We find that Ide-/- NOD harbor fewer diabetogenic T cells and reduced numbers of CD8+ T cells recognizing the dominant autoantigen insulin and islet-specific glucose-6-phosphatase catalytic subunit-related protein (IGRP). Using in vitro digestions and cellular antigen presentation assays, we show that generation of the dominant insulin epitope B15-23 involves both the proteasome and IDE. IDE deficiency attenuates MHC-I presentation of the immunodominant insulin epitope by beta cells to cognate CD8+ T cells. Consequently, Ide-/- islets display reduced susceptibility to autoimmune destruction upon grafting, and to killing by insulin-specific CD8+ T cells. Moreover, Ide-/- mice are partly resistant to disease transfer by CD8+ T cells specific for insulin but not for IGRP. Thus, IDE has a dual role in beta cells, regulating ER stress and proliferation while at the same time promoting insulin-directed autoreactive CD8+ T cell responses.